Jihad Perang dalam Perspektif Hukum Islam: (Kajian Pemikiran Muhammad Abu Zahrah) - Moh. Irfan (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to describe and analyze Abu Zahrah's thoughts on war jihad in the perspective of Islamic law. This type of research is library research (library research) with a qualitative approach. The data collection technique used documentation techniques then analyzed with content analysis techniques (content analysis). The research results show: (1) Jihad war in Islam is permissible with conditions in order to defend oneself from enemy attacks, or to be expelled from their territory or country, or if their agreement is betrayed. Jihad war can become mandatory if the Muslims are really in a state of emergency, and that too is the level of their obligation as fardhu kifayah. (2) The foundations of the war jihad of the Prophet Muhammad SAW were built on the basis of mercy (compassion), karamatul insan (human honor), and al-'adalah (justice). (3) The procedures for war jihad must be pursued in correct and good ways, namely by knowing and fulfilling its requirements, understanding its objectives, straightening one's motivation, obeying its boundaries, and implementing ethics.